(untitled) (Dhaka University Journal of Biological Sciences, 2022)
Northern River Terrapin, Batagur baska, is an ecologically extinct species in Bangladesh. The ‘Project Batagur’ has undertaken some important initiatives to resuscitate the nearly deceased population through captive breeding at Bhawal National Park, Gazipur, Bangladesh. We conducted a study on breeding biology of B. baska from May 2016 to June 2017 in the project site. Four adult females and three adult males comprised breeding pair in the study site. Male Batagur baska developed black colouration on head and neck, with rich crimson on dorsal portion of the neck during breeding season. During our study, we observed paired basking behaviour rather courtship and parental care. We found three nests from mid-March to first week of April. Females laid eggs at night and a total of 67 eggs were extracted from three nests; eggs were elliptical and whitish in colour. Clutch size varied from 18 to 28 eggs. There was significant positive correlation between clutch size and nest diameter (p = 0.03). The relationship was also positive and significant between egg weight and diameter (p = 0.01).The size of the egg was not related with the size of breeding females (r = 0.143).Average incubation period was (68.26 ± 5.23) days and there was significant negative relationship with temperature (p= 0.000), clutch size (p = 0.001), and hatching success (p = 0.004). Hatching success was also negatively co-related with temperature (p= 0.001). Hatching started in May and ended in the first week of June 2017 with mean hatching success of 91%. Simple linear regression showed positive relationship between egg length and hatchlings’ carapace length, plastron length, and height. We also found positive relationship between egg diameter and hatchlings weight, and carapace width. This study can be used as a protocol for captive breeding and rearing activities of threatened chelonians around the world. Dhaka Univ. J. Biol. Sci. 31(1): 67-78, 2022 (January)